The Impact Of Employee Voices On Leadership Perspectives - Grace Yulianti (Journal of Economic and Leadership, 2024)
This research explores the phenomenon of heedful challenging in organizational contexts, focusing on the role of organizational culture and leadershipstudy. The term "heedful challenging" describes proactive voice practices by lower-power staff members with the goal of enhancing innovation and corporate decision-making. The review synthesizes recent empirical studies to elucidate how supportive organizational cultures and transformational leadership styles facilitate heedful challenging, enhancing employee empowerment, job satisfaction, and organizational adaptability. Key findings highlight the positive outcomes of thoughtful challenge, such as better organizational learning and decision-making procedures. Barriers such as fear of reprisals in hostile situations highlight how important it is to promote transparency and trust. The consequences for practitioners stress how crucial it is to foster inclusive cultures and use transformational leadership techniques in order to encourage employee voice activities.